Proceso de atención de enfermería en adolecente con traumatismo craneoencefálico. - Maldonado Tomalo, Nayelhy Liseth (2022)
Cranioencephalic traumatism are alterations that cause damage to the brain that are generated by blows against objects that many of the cases do not reach to break the skin, this will cause a deficit in consciousness, cognitive, perceptive malfunction and daily activities such as speaking and walk. (Charry et al., 2017). The prevalence is 200 per 100,000 inhabitants, the most frequent cause being traffic accidents (70%) followed by violent behavior and/or falls from height depending on the geographical area. (Charry et al., 2017). The present clinical case is focused on a 12-year-old adolescent who went to the San Francisco de Quito Hospital through the emergency area, after suffering an accident when falling from the terrace, the mother reports that her son hit his head and He was found lying down with an appearance of disorientation, so he went to the hospital for an emergency, the patient was admitted walking and reported a headache and also a lot of pain in the left upper limb, he did not vomit, Glasgow 15/15 he was admitted for his respective evaluation by the doctor, and the respective care of the nursing staff. The clinical case study has as its general objective: Apply the nursing care process through a nursing diagnosis in a 12-year-old male patient with traumatic brain injury in the Pediatrics area of the San Francisco General Hospital in Quito.